Pikareskni pisec - Rott, Zala (Keria (Ljubljana), 2009)
The article focuses on two novels, Apuleius' Metamorphoses and the Spanish picaresque novel, Lazarillo de Tormes. It explores their structural similarities - the first-person narrator, the retrospective account of a life under various masters, Fortune as a key mechanism in the narrative - as well as the less obvious resemblances in the themes of speech, writing, and literary ambition.
Keywords: antični roman; Apuleius Madaurensis, Lucius: Metamorfoze; La vida de Lazarillo de Tormes; latinska književnost; literarne študije; pikareskni roman; pripovedovalec; rimska književnost; španska književnost; Življenje Lazarčka s Tormesa